2019
DOI: 10.3892/etm.2019.8392
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of immune response by S‑1‑propenylcysteine through autophagy‑mediated protein degradation (Review)

Abstract: Autophagy is a key event in cellular recycling processes due to its involvement in the intracellular degradation of proteins. It has been demonstrated that S-1-propenylcysteine (S1PC), a characteristic sulfur compound in aged garlic extract, induces the activation of autophagy. S1PC degrades the adaptor protein myeloid differentiation response protein 88 (MyD88) of downstream of Toll-like receptor (TLR) by activating autophagy in vitro and in vivo. The degradation of MyD88 inhibits the TLR signaling pathway, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…S1PC also modulates the immune response by inducing autophagy, a key event in cellular recycling processes due to its involvement in the intracellular degradation of proteins [ 26 ]. S1PC degrades the adaptor protein myeloid differentiation response protein 88 (MyD88) of downstream of Toll-like receptor (TLR) by activating autophagy [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S1PC also modulates the immune response by inducing autophagy, a key event in cellular recycling processes due to its involvement in the intracellular degradation of proteins [ 26 ]. S1PC degrades the adaptor protein myeloid differentiation response protein 88 (MyD88) of downstream of Toll-like receptor (TLR) by activating autophagy [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…S1PC also modulates the immune response by inducing autophagy, a key event in cellular recycling processes due to its involvement in the intracellular degradation of proteins [ 26 ]. S1PC degrades the adaptor protein myeloid differentiation response protein 88 (MyD88) of downstream of Toll-like receptor (TLR) by activating autophagy [ 26 ]. The degradation of MyD88 inhibits the TLR signaling pathway, including the phosphorylation of IL-1 receptor associated kinase 4 (IRAK4) and nuclear factor (NF)-kappa β p65, that leads to the inhibition of IL-6 production and C-C motif chemokine ligand 2 (Ccl2) mRNA expression [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aged garlic extract (AGE) is one of the garlic products manufactured by aging garlic (Allium sativum L.) in the water-ethanol mixture for more than 10 months at room temperature [18]. AGE contains several bioactive sulfur-containing amino acids, including S-allyl-Lcysteine, S-1-propenyl-L-cysteine (S1PC), and S-allyl-L-mercaptocysteine that possess such properties as antioxidation [19,20], anti-inflammation [21][22][23], and immunomodulation [24][25][26]. A clinical trial on patients with mild to moderate periodontitis demonstrated that daily intake of AGE for 4 months improved gingival bleeding index [27].…”
Section: Introductionmentioning
confidence: 99%
“…Aged garlic extract (AGE) is one of the garlic products prepared by the soaking of garlic with aqueous ethanol for more than 10 months at room temperature (23). AGE and its bioactive sulfur-containing amino acids, S-allylcysteine, S-1-propenylcysteine, and S-allylmercaptocysteine, possess favorable properties such as antioxidation (24,25), anti-inflammation (26-28), immunomodulation (29)(30)(31), and anti-cancer activities (32). Several human clinical studies have demonstrated that AGE improves hypertension (33), atherosclerosis (34), and metabolic syndrome (35).…”
Section: Introductionmentioning
confidence: 99%